Penyuluhan dan Penerapan Teknologi Tepat Guna untuk Peningkatan Produksi Garam Krosok melalui Sistem Tunnel dan Filter Inlet Outlet (FIO) di Desa Tedunan, Demak, Jawa Tengah - Cahyo Wulandari; Muhammad Galih; Fachri Haidar Kuncoro; Fatimah Az Zahra (Direktorat Pengabdian kepada Masyarakat, 2023)
The potential for salt in Tedunan Village, Wedung District, and Demak Regency is very large, but it still maximized. Two factors influence the amount of salt, namely climatic conditions and the sources of raw materials. Hot temperatures and scorching sunlight make the climate conditions in Tedunan Village very suitable for salt farming. Abundant sources of raw materials, with the location of the village not far from the sea making it very easy to obtain raw materials for making salt from estuaries. The sluice gate that separates seawater and freshwater also plays a vital role in maintaining the quality of raw materials. With the high potential for salt in Tedunan Village, this community service is conducted to assist salt farmers in Tedunan Village by introducing applying appropriate technology, which is expected to solve salt production problems. The community service results show that the main problem is that the seawater used as a raw material contains a lot of pollutants. The next problem is that salt production must stop during the rainy season, rainwater will change the salt content in seawater which ultimately makes it difficult for salt farmers to produce salt during the rainy season. Collaborating with village officials and the salt group in Tedunan Village, made the community service process more easy. The Village government helps provide relevant data for setting targets, then salt producers groups express problems that are currently happening and will occur based on experience. Research activities, education, and application of appropriate technology which includes FIO and tunnel systems, can have an impact on salt farmers in Tedunan Village.